Penerapan Ornamen Motif Kaligrafi Khuffi Pada Masjid Jami Al-Irsyad - Latifah, Ima Siti; Darmawan, Cherry (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2021)
This paper describes the application of khuffi calligraphy ornaments to the Al-Irshad Mosque. Al-Irsyad Mosque is a mosque that implements modern style without removing the image of the mosque as a place of worship for Muslims. Ornament is a form of visual art in the form of a symbol that has its own meaning and is used as decoration or accent of room decoration. Calligraphy ornaments are a form of absorption of Arabic letters arranged in proportion so that they form a work of art that can be seen visually without changing the meaning of the sentence used. Calligraphy Ornaments khat khuffi is a type of calligraphy ornament with angular formations. This khat is commonly used as a ornament of bagunan with the concept of modern Islamic architecture. because this form of khat has a novelty nature. In addition, another discussion that was put forward was that of the characteristics of form, function and meaning in each ornament of calligraphy khuffi. This research method uses descriptive qualitative method by identifying the meaning, function and continuity of the use of khuffi calligraphy motifs at Al-Irsyad Mosque. The result that will be achieved is what is the continuity of the application of the khuffi calligraphy motif at the Al-Irshad Mosque which has a modern style.